1995
DOI: 10.1074/jbc.270.40.23801
|View full text |Cite
|
Sign up to set email alerts
|

The Saccharomyces cerevisiae RIB4 Gene Codes for 6,7-Dimethyl- 8-ribityllumazine Synthase Involved in Riboflavin Biosynthesis

Abstract: 6,7-Dimethyl-8-ribityllumazine, the immediate biosynthetic precursor of riboflavin, is synthesized by condensation of 5-amino-6-ribitylamino-2,4(1H,3H)-pyrimidinedione with 3,4-dihydroxy-2-butanone 4-phosphate. The gene coding for 6,7-dimethyl-8-ribityllumazine synthase in Saccharomyces cerevisiae (RIB4) has been cloned by functional complementation of a mutant accumulating 5-amino-6-ribitylamino-2,4(1H,3H)-pyrimidinedione, which can grow on riboflavin-or diacetylbut not on 3,4-dihydroxy-2-butanone-supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…The rib3 null mutant used in this study shows an auxotrophic requirement of riboflavin for growth on glucose as reported previously (3). In contrast, the rib3 point mutant, like other pet mutants, grows on glucose in the absence of added riboflavin.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The rib3 null mutant used in this study shows an auxotrophic requirement of riboflavin for growth on glucose as reported previously (3). In contrast, the rib3 point mutant, like other pet mutants, grows on glucose in the absence of added riboflavin.…”
Section: Discussionmentioning
confidence: 72%
“…The mutant has been determined to have a point mutation in RIB3, a conserved gene of which the product, 3,4-dihydroxy-2-butanone-4-phosphate synthase (DHBP 1 synthase), catalyzes the first step in the riboflavin biosynthetic pathway (2). Complementation of aE280/U1 by RIB3 was unexpected in view of previous studies indicating that rib3 mutants require riboflavin for growth (3). The lack of correspondence in the phenotype of the rib3 point mutant and a mutant with a complete deletion of RIB3 prompted us to examine the biochemical properties of the mutant further.…”
mentioning
confidence: 99%
“…Sequence alignment of LS homologs. The amino acid sequence of the spinach LS precursor is aligned to the corresponding sequences from E. coli (8), B. subtilis (11), A. pleuropneumoniae (9), P. phosphoreum (10), and S. cerevisiae (12). Residues that are identical in at least four of the sequences are indicated by open squares, and those that are identical in all six sequences are indicated by filled black circles.…”
Section: Methodsmentioning
confidence: 99%
“…Section 1734 solely to indicate this fact. (12). In all cases, the subunit molecular mass of the encoded protein is small, ranging in size from ϳ16 to 17 kDa.…”
mentioning
confidence: 99%
See 1 more Smart Citation